Muon reconstruction and identification efficiency in ATLAS using the full Run 2 pp collision data set at √s = 13 TeV - Aad, Georges; Andrei, George Victor; Bartels, Falk; Bolz, Arthur; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; et al. (The European physical journal. C, Particles and fields, 2021)
This article documents the muon reconstruction manednitdfeonrt1iﬁ3c9aftibo−n1eofﬁf cpipenccoylloisbitoanindeadtabyatt√hesA=TL1A3 STeeVxpceorli-lected between 2015 and 2018 during Run 2 of the LHC. The increased instantaneous luminosity delivered by the LHC over this period required a reoptimisation of the criteria for the identiﬁcation of prompt muons. Improved and newly developed algorithms were deployed to preserve high muon identiﬁcation efﬁciency with a low misidentiﬁcation rate and good momentum resolution. The availability of large samples of Z → μμ and J/ψ → μμ decays, and the minimisation of systematic uncertainties, allows the efﬁciencies of criteria for muon identiﬁcation, primary vertex association, and isolation to be measured with an accuracy at the per-mille level in the bulk of the phase space, and up to the percent level in complex kinematic conﬁgurations. Excellent performance is achieved over a range of transverse momenta from 3 GeV to several hundred GeV, and across the full muon detector acceptance of |η| < 2.7.
Gesehen am 13.11.2021
The ATLAS collaboration: G. Aad, V. Andrei, F. Bartels, A.E. Bolz, M.M. Czurylo, S.J. Dittmeier, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M. Klassen, A. Krishnan, T. Mkrtchyan, F. Napolitano, P.S. Ott, D.F. Rassloff, A. Schoening, H.-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, X. Yue [und viele weitere]